Curriculum restructuring in Higher Education after the Bologna Process: a new pedagogic regime? - Karseth, Berit (Revista Española de Educación Comparada, 2006)
By adopting the Bologna Process as the frame of reference this article discusses the ongoing policy of curriculum restructuring in higher education.The analysis is based on policy documents produced on the European scene and documents which describe the restructuring process in the highereducation system of Norway. The article shows how the new discourse presented by the Bologna Process challenges the traditional curriculum discourses in higher education. The credit accumulation and transfer discourse asks for a curricular framework which enhances mobility,employability and competitiveness. Although the rhetoric calls attention to institutional autonomy the curriculum restructuring represents a standardisation of higher education whereby the management of credit transfer and accumulation becomes the salient task. The aim is to develop a highly reliable space of higher education which is manageable and predictable. Although a flexible curriculum approach together with a studentcentred pedagogy are advocated, the Bologna Process can be read as a rational programme that tends to create a discourse for the governing of the student (the self) in light of the objectives already set. Tras adoptar el proceso de Bolonia como punto de referencia, este artículo se encarga de analizar la corriente política de reestructuración de currículos en educación superior. El análisis se basa en documentos producidos en el ámbito europeo, algunos dedicados al estudio del proceso de reestructuración de la educación superior en Noruega. El artículo muestra cómo el nuevo discurso presentado por el proceso de Bolonia, pone en entredicho los discursos tradicionales en educación superior en referencia al currículo. La acumulación y transferencia de créditos necesitan moverse en un marco más actual, que realce la movilidad, empleabilidad y competitividad. Aunque la retórica pueda ser importante en términos de autonomía institucional, la reestructuración curricular representa una estandarización a nivel de Educación Superior, por la cual la transferencia y acumulación de créditos se convierte en una tarea saliente. El objetivo es desarrollar un espacio fiable para la educación superior que sea manejable y predecible. Aunque se abogue por un tratamiento flexible del currículo y una pedagogía centrada en el estudiante, el proceso de Bolonia puede ser contemplado como un programa racional que tiende a crear un discurso propio para el control estudiantil, basado en objetivos fijados con anterioridad